Recurrent Sites for New Centromere Seeding - Ventura, Mario; Weigl, Stefania; Carbone, Lucia; Cardone, Maria Francesca; Misceo, Doriana; Teti, Mariagrazia; D'Addabbo, Pietro; Wandall, Annelise; Björck, Erik; de Jong, Pieter J.; She, Xinwei; Eichler, Evan E.; et al. (Genome Research, 2004)
Using comparative FISH and genomics, we have studied and compared the evolution of chromosome 3 in primates and two human neocentromere cases on the long arm of this chromosome. Our results show that one of the human neocentromere cases maps to the same 3q26 chromosomal region where a new centromere emerged in a common ancestor of the Old World monkeys ∼25-40 million years ago. Similarly, the locus in which a new centromere was seeded in the great apes' ancestor was orthologous to the site in which a new centromere emerged in the New World monkeys' ancestor. These data suggest the recurrent use of longstanding latent centromeres and that there is an inherent potential of these regions to form centromeres. The second human neocentromere case (3q24) revealed unprecedented features. The neocentromere emergence was not accompanied by any chromosomal rearrangement that usually triggers these events. Instead, it involved the functional inactivation of the normal centromere, and was present in an otherwise phenotypically normal individual who transmitted this unusual chromosome to the next generation. We propose that the formation of neocentromeres in humans and the emergence of new centromeres during the course of evolution share a common mechanism.
10.1101/gr.2608804